The Role of the Muslim Community in the Establishment of the Jayapura’s Jami Mosque during the Dutch East Indies Era in 1943 - Muhammad Aqil; Ade Sopyan Hadi Hadi; Kulyasin yasin; Akbar Guntoro Praseto akbar (JUPE : Jurnal Pendidikan Mandala, 2026)
This study examines the role of the Muslim community in the establishment of the Jayapura Jami Mosque in 1943 and its significance in the socio-religious life of the Muslim community in Jayapura during the Dutch East Indies era. This  study uses a qualitative approach with historical methods through the stages of heuristics, source criticism, interpretation, and historiography. The results show that the existence of the Muslim community in Jayapura is related to the migration process from Eastern Indonesia regions such as Buton, Ternate, Tidore, Halmahera, Waigeo, and Salawati, which was influenced by Jayapura's development as a colonial center and port. The Muslim community then built social solidarity in maintaining religious identity amidst colonial domination and Christian missions. This was manifested through the independent establishment of the Jayapura Jami Mosquein 1943. The mosque serves not only as a place of worship, but also as a center for education, preaching, and social activities, and has important historical value in the development of Islam in Papua, including the period of Papua's integration into Indonesia. This study confirms the significant contribution of the Muslim community in shaping socio- religious life in Jayapura and enriches the historiography of Islam in Papua.